Beispiel Nr: 17
$ \text{Gegeben:} ax^{2}+bx+c=0 \\ \text{Gesucht:} \\ \text{Lösung der Gleichung} \\ \\ ax^{2}+bx+c=0 \\ \textbf{Gegeben:} \\ x^2-8x+15 =0 \\ \\ \textbf{Rechnung:} \\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline \\ 1x^{2}-8x+15 =0 \\ x_{1/2}=\displaystyle\frac{+8 \pm\sqrt{\left(-8\right)^{2}-4\cdot 1 \cdot 15}}{2\cdot1} \\ x_{1/2}=\displaystyle \frac{+8 \pm\sqrt{4}}{2} \\ x_{1/2}=\displaystyle \frac{8 \pm2}{2} \\ x_{1}=\displaystyle \frac{8 +2}{2} \qquad x_{2}=\displaystyle \frac{8 -2}{2} \\ x_{1}=5 \qquad x_{2}=3 \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ \\ x^{2}-8x+15 =0 \\ x_{1/2}=\displaystyle -\frac{-8}{2}\pm\sqrt{\left(\frac{\left(-8\right)}{2}\right)^2- 15} \\ x_{1/2}=\displaystyle 4\pm\sqrt{1} \\ x_{1/2}=\displaystyle 4\pm1 \\ x_{1}=5 \qquad x_{2}=3 \end{array}\\ \end{array}$